HUBUNGAN KELANCARAN PRODUKSI ASI TERHADAP PEMBERIAN ASI EKSKLUSIF PADA IBU YANG MEMILIKI BALITA USIA 7-12 BULAN DI DESA CIPANG KIRI HULU - Wahyuny, Romy; Fitria, Rahmi; Ermiza, Ermiza; Anjeli, Anista (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Exclusive breastfeeding during the first six months of an infant’s life is essential to support optimal growth and development. However, the coverage of exclusive breastfeeding in Indonesia has not yet reached the expected target. Smooth breast milk production is one of the crucial factors in the success of exclusive breastfeeding. This study aims to determine the relationship between the smoothness of breast milk production and exclusive breastfeeding among mothers with children aged 7–12 months in Cipang Kiri Hulu Village, Rokan IV Koto District. This research used a quantitative approach with a cross-sectional design. A total of 30 breastfeeding mothers were selected using a purposive sampling technique. Data were collected through questionnaires and analyzed using the chi-square test. The results showed a significant relationship between smooth breast milk production and exclusive breastfeeding (p = 0.002), with an Odds Ratio of 28.500 (95% CI: 2.649–303.638). It can be concluded that mothers with smooth breast milk production are 28.5 times more likely to provide exclusive breastfeeding compared to those with less smooth milk production. Therefore, support and education for breastfeeding mothers need to be enhanced to promote smooth breast milk production and the success of exclusive breastfeeding. The researcher assumes that the smoothness of breast milk production greatly influences the success of exclusive breastfeeding. Keywords: Smooth Breast Milk, Exclusive Breast Milk, Breastfeeding Mothers, Toddlers 7–12 Months